Policy Implementation of Waste Management at Bintang Mangrove Waste Bank, Surabaya City - Jannah, Eka Maidhatul; Wibawani, Sri (Journal of Public Representative and Society Provision, 2025)
This study aims to describe and analyze the implementation of waste management policies at the Bintang Mangrove Waste Bank in Surabaya City, based on the Minister of Environment and Forestry Regulation No. 14 of 2021 and Surabaya Regional Regulation No. 1 of 2019. The research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The theoretical framework is based on the Policy Implementation theory by Randall B. Ripley and Grace A. Franklin (1986:232). The findings indicate that policy implementation was carried out through two main aspects: waste reduction and waste handling. Reduction efforts included recycling and reusing waste, which had both economic and environmental impacts. Waste handling involved sorting, collecting, processing, and delivering waste. The Bintang Mangrove Waste Bank also played a significant role in educating the community through the "River School" program and encouraged behavioral changes in sustainable waste management. Although the implementation has been relatively successful, challenges remain such as limited human resources for waste sorting and low market demand for recycled products. The study concludes that the Bintang Mangrove Waste Bank has effectively realized the 3R principles and implemented a circular economy model that provides ecological, educational, and economic benefits to the community.